Effect of a multimodal continuing professional development initiative on HIV testing in primary care in British Columbia, Canada - Brenna M. Lynn; Jennifer A. Barrows; Vivian W.Y. Lam; Vernon R. Curran (AIDS Research and Therapy)
Abstract Introduction Many persons are unaware of HIV infection until they present in an advanced stage of the disease. Diagnosing HIV infection in its earliest stages reduces morbidity and mortality and contributes to improved public health. Increased testing for HIV is critical for prevention, and primary care providers play an essential role in early HIV screening. However, lack of knowledge and confidence are barriers to the adoption of screening practices. Continuing professional development (CPD) may enhance greater HIV testing uptake amongst primary care providers by improving awareness and comfort. This paper aims to report on the impact of a multimodal CPD initiative to increase HIV screening and test ordering across primary care settings in British Columbia, Canada. Methods The ‘HIV Testing Initiative in Family Practice’ was designed as a multimodal education strategy to encourage family physicians to adopt routine HIV testing in their practices. The initiative encompassed a variety of core and supplementary educational activities, including interactive in-person CPD workshops, practice resources, and patient education materials. An interrupted time series study was undertaken to evaluate the effect on HIV test ordering before and after workshop participation. Participants also completed post-workshop surveys to assess satisfaction. Results In total, 316 individuals participated in the core educational activities of the initiative. The number of HIV tests ordered increased significantly amongst participants following workshop participation (p < .001). HIV test ordering increased for both rural and urban providers with no significant difference (p = .075) on the number of tests ordered between these groups. Participants were very satisfied with workshop participation, with an overall mean satisfaction rating of 4.78 (out of 5) and reported high satisfaction with the format (4.64 out of 5) and interactivity (4.76 out of 5) features across the workshops. Discussion The findings suggest that the introduction of a multimodal CPD intervention may have effected change in family physicians’ HIV testing practices. The HIV testing rates of physicians who had participated in CPD workshops increased significantly, and participant evaluation data indicated a greater understanding of the rationale for routine HIV testing, as well as an increase in comfort with recommending HIV tests to patients.